The early Palaeogene transition from thin-skinned to thick-skinned shortening in the Potosí uplift, Sierra Madre Oriental, northeastern Mexico. Issue 2 (22nd January 2021) - Williams, Stewart A.; Singleton, J. S.; Prior, M. G.; Mavor, S. P.; Cross, G. E.; Stockli, D.F.
ABSTRACT: The central Sierra Madre Oriental in Mexico developed primarily in the Late Cretaceous to early Palaeogene as a thin-skinned fold belt above a décollement hosted in Jurassic evaporite. In some regions shortening transitioned to sub-décollement structural levels, resulting in thick-skinned uplifts such as the Potosí uplift in Nuevo León. Thick-skinned deformation in the Potosí uplift involved folding of sub-décollement strata into an NNW-trending anticlinorium, cleavage development, thrust and conjugate strike-slip faulting, and extension fractures associated with barite mineralization. These structures consistently record subhorizontal shortening, directed 52–65° in the southern uplift, 69–72° in the northern uplift. Palaeocene to mid-Eocene zircon (U-Th)/He cooling dates record the timing of exhumation associated with thick-skinned uplift and suggest a continuation of shortening rather than a separate tectonic event. Zircon (U-Th)/He dates across the southern Potosí uplift and the Aramberri uplift, 50 km to the south, range from 66–53 Ma, whereas dates in the northern part of the Potosí uplift range from 49–44 Ma. We attribute the transition to thick-skinned shortening to the mechanical strengthening of a planar décollement as rheologically weak evaporite was evacuated beneath synclinal keels of detachment folds. Along-strike differences in timing of exhumation and shortening directions may relate to differences in mechanical stratigraphy. Thicker intervals of evaporite in the northern uplift allowed thin-skinned shortening to continue while the southern uplift transitioned to thick-skinned shortening as the evaporite décollement was exhausted. As a result, stress-strain trajectories in the northern uplift refracted clockwise during continued deformation. Our findings provide new insight into the structural evolution of the Potosí uplift and may provide a framework for studying other thick-skinned uplifts in the orogen, and more generally orogenic belts that record a transition in deformation styles during progressive shortening.